PENERAPAN MODEL EOQ PADA APLIKASI INVENTORY CONTROL BERBASIS WEB DI PERUSAHAAN - Adysha Puspa Dewi; Amri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Inventory management is one of the essential components of a company’s operations. Problems arise when inventory management is still conducted manually, making it difficult for companies to determine updated stock levels, record incoming and outgoing goods, and generate routine reports. These limitations can negatively affect future inventory planning, as stock replenishment is often based solely on estimated needs or performed only when items are out of stock. To address these issues, an inventory management application is needed to support effective inventory control.This study employs an object-oriented approach and the prototype development model. Inventory planning is supported by the Economic Order Quantity (EOQ) model to determine optimal order quantities. The system was designed using Unified Modeling Language (UML), developed with the PHP programming language, and tested using the black-box testing method. The results show that the web-based inventory control application integrated with the Economic Order Quantity method functions effectively and can assist companies in improving inventory management and planning processes.